2019
DOI: 10.1093/ptj/pzz101
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Exercise in the Treatment of Primary Dysmenorrhea: A Systematic Review and Meta-Analysis

Abstract: Background Dysmenorrhea is a health problem with a high impact on health and society. Some drugs have been shown to be effective at treating dysmenorrhea. Therapeutic exercise is another option for reducing the symptomatology of this health problem, with a low cost and the absence of side effects. Purpose The purposes of this review were to study the efficacy of physical exercise for pain intensity in primary dysmenorrhea and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 38 publications
2
41
0
5
Order By: Relevance
“…Our results showed that some students give up the practice of sports. In contrast, previous studies [10,45] reported how the practice of certain types of sports can prevent or decrease the intensity of PD. Furthermore, exercise among women with PD has been found to enhance their quality of life [46,47].…”
Section: Discussionmentioning
confidence: 71%
“…Our results showed that some students give up the practice of sports. In contrast, previous studies [10,45] reported how the practice of certain types of sports can prevent or decrease the intensity of PD. Furthermore, exercise among women with PD has been found to enhance their quality of life [46,47].…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, it has been identified that most women self-medicate with sub-therapeutic doses, which results in an unsuccessful approach [ 45 ]. Health professionals have an important role to play in this menstrual problem, as they can individually evaluate and detect secondary dysmenorrhea, advise on risk factors and protective factors, on the correct pharmacological approach, as well as report on non-pharmacological methods with proven efficacy that have fewer side effects, such as those based on physical exercise [ 28 , 46 ]. However, young women usually receive information about menstruation within their own families, from their mothers or sisters, yet, they are not sufficiently prepared to meet their needs [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis showed that physical exercise resulted in an improvement in both intensity and duration of pain in those who suffer from dysmenorrhea. This study should be interpreted with care however, as the type of exercise that leads to these positive results is varied [ 7 ].…”
Section: Discussionmentioning
confidence: 99%